The Effect of Administration Ginger and Lemongrass Drink on Interleukine 6 Football Player After Exercise - adnan, Miftahul; Afifah, Diana Nur; Anjani, Gemala; Susanto, Hardhono; Noer, Etika Ratna; Widodo, Sumardi (Universitas Negeri Semarang, 2024)
Physical exercise can increase the production of free radicals. Free radical can trigger oxidative stress and inflammation. Ginger and lemongrass has bioactive compound that function as antioxidant and antiinflammatory. This study aim to determine the effecs of giving ginger and lemongras drink on IL6 level in football player. Quasi experimental study with pre and post control group design. The subject were 24 football player divided 2 namely control and intervention group. The intervention group given a ginger and lemongrass drink. The control group was only given brown sugar drink. The intervention are given after exercise for 28 days. Blood samples were collected and tested after exercise. Interleukine 6 were measured using the ELISA Method. Our result showed there was differences in interleukine 6 after giving ginger and lemongrass drink (p=0.004). The delta of interleukine 6 level after intervention was 3.24 pg/ml. Conclusion this research are there was a decrease in interleukine 6 level after giving ginger and lemongrass drink for 28 days to football players after exercise.